Sanjad-Sakati syndrome with corneal opacity in a Palestinian neonate: case report - Allam Fayez Abuhamda; Aymen Mohammed Elsous (Hygeia Press di Corridori Marinella, 2020)
Sanjad-Sakati syndrome is an autosomal recessive disorder found mainly in people of Arabian origin. This is a report of a Palestinian premature (35 weeks gestation) newborn who was part of twins and had this rare disease. The syndrome comprises congenital hypoparathyroidism, hypocalcaemia, seizure, severe growth retardation, low IQ and typical facial features. In addition, the baby had corneal opacity, although his elder brother with the same syndrome had not. Supportive treatment in the form of oral vitamin D and calcium are often offered to these children to treat hypocalcaemia.